Cascade Biocatalysis for Sustainable Asymmetric Synthesis: From Biobased l‐Phenylalanine to High‐Value Chiral Chemicals. Issue 38 (11th August 2016) - Zhou, Yi; Wu, Shuke; Li, Zhi
Abstract: Sustainable synthesis of useful and valuable chiral fine chemicals from renewable feedstocks is highly desirable but remains challenging. Reported herein is a designed and engineered set of unique non‐natural biocatalytic cascades to achieve the asymmetric synthesis of chiral epoxide, diols, hydroxy acid, and amino acid in high yield and with excellent ee values from the easily available biobasedl ‐phenylalanine. Each of the cascades was efficiently performed in one pot by using the cells of a single recombinant strain over‐expressing 4–10 different enzymes. The cascade biocatalysis approach is promising for upgrading biobased bulk chemicals to high‐value chiral chemicals. In addition, combining the non‐natural enzyme cascades with the natural metabolic pathway of the host strain enabled the fermentative production of the chiral fine chemicals from glucose. Abstract : All fine : Asymmetric synthesis of a chiral epoxide, diols, a hydroxy acid, and an amino acid in high yield and with excellent ee value from biobasedl ‐phenylalanine was achieved with engineered whole‐cell biocatalysts containing designed non‐natural enzyme cascades, respectively. Fermentative production of the chiral chemicals from glucose was also demonstrated by combining the non‐natural cascades with the metabolic pathway of the host.